Distribusi Polimorfisme Gen Transforming Growth Factor Beta-1 (T869C) Pada Pasien Psoriasis Di Kota Medan, Sumatera Utara - Rahmiwita, Rahmiwita; Siregar, Yahwardiah; Ichwan, Muhammad (Universitas Muhammadiyah Sumatera Utara, 2021)
Psoriasis is a chronic inflammatory skin disease with a prevalence in the world around 2-3%. TGF-?1 is a growth factor that has a polymorphism in its genes. The TGF-?1 gene polymorphism plays a role in the pathogenesis of psoriasis. This is a descriptive study with a simple random sampling technique. This study was conducted on the strored of DNA specimens collected from 62 psoriasis patients comprising 33 women and 29 men. This study aims to determine the frequency distribution of the TGF-?1 gene polymorphism (T869C) in patients with psoriasis. The TGF-?1 gene polymorphism (T869C) was determined using PCR-based restricted fragment length polymorphism (PCR-RFLP). TC genotype was the most prevalent (50%) of TGF-?1 (T869C) gene polymorphism in psoriasis patients, followed by TT genotype (6.5%) and CC (43.5%). TC variant is the most variant of TGF-?1 (T869C) gene polymorphism in psoriasis sufferers in Medan